A mishap in guided surgery for All-on-4™ technique: A case report (Indian Journal of Case Reports, 2024)
A 63-year-old male patient, who had a severely resorbed edentulous maxillary arch and partially edentulous mandibular arch decided on the implant-supported fixed treatment option to replace the edentulous maxillary arch. The fully guided implant placement that utilizes the computer-generated guide is more accurate than traditional surgical guides and free-hand placements. The researchers have correlated possible implant failure risk factors with age, sex, smoking, type of edentulism, bone quality and volume, implant location, angulation, diameter, length, and various systemic factors. This case report demonstrated the failure cause of virtually planned anterior implants in All-on-4 and how to manage it by free-hand surgery without surgical guides.